SYNTHESIS OF SUPPORTED CATALYST FOR CONVERSION OF METHANE AND CARBON DIOXIDE TO SYNGAS - KAMARUDIN, MUHAMMAD HAZIM (IRC, 2017)
The rising of technology development throughout the world leads towards the increasing in global temperature. One of the major caused that lead to global warming is the presence of high concentration of greenhouse gasses such as methane, carbon dioxide, nitrogen oxide in the atmosphere. In order to reduce the effect of global warming, many researchers have carried out experiment to convert the greenhouse gasses towards something beneficial and environmental friendly. One of the well-known process is converting methane (CH4) and carbon dioxide (CO2) to produce syngas. To improve the conversion rate of methane and carbon dioxide, various catalysts have been used by researchers. Among them, the most typically used is Nickel (Ni). The performance of Ni can be enhanced by adding catalyst support. There are many types of support that had been studied to improve activity, stability and selectivity of Nickel such as ZrO2, CeO2, K2O and MgO. On top of everything, the difference of this project with other projects is the uses of chemical treatment of Kaolinite as catalyst support. The catalyst synthesized first by using simple dissolution method and tested in the tubular reactor which operates at 850℃ for 4 hours. Then, the catalyst characterized by using several ways including X-Ray Fluorescence analysis (XRF) and Scanning Electron Microscopy-Energy Dispersive X-ray spectroscopy (SEM-EDX).